Preparation and Characterization of a New Monoclonal Antibody Specific Against Lawsonia intracellularis and Its Application in Indirect Immunofluorescence and Immunocytochemistry Assay - Xiao, Ning; Li, Jiannan; Li, Minxue; Hu, Yuting; Lin, Huixing; Fan, Hongjie (Frontiers in Veterinary Science, 2021)
Proliferative enteropathy (PE) is an infectious enteric disease caused by Lawsonia intracellularis (L. intracellularis) and is endemic in pig herds worldwide. However, a L. intracellularis–specific monoclonal antibody plays an important role in the evaluation of L. intracellularis infection in vitro. Therefore, the objective of this study was to produce, identify the characteristics a new monoclonal antibody against outer membrane protein (Omp2) of L. intracellularis and application it in an indirect immunofluorescence assay (IFA) and immunocytochemistry (IHC). The results indicated that three highly specific monoclonal antibodies against the Omp2 protein (4D9, 3G2, and 7G5) of L. intracellularis were obtained by using purified Omp2 as an immunogen, the titres of ascitic fluids of 4D9, 3G2, and 7G5 cells were 1:2048000, 1:512000 and 1:256000, respectively. IFA analysis showed that the 4D9, 3G2, and 7G5 have no cross-reactivity with other enteric bacteria commonly found in the ilea of pigs or closely related to L. intracellularis, such as Desulfovibrio, Bilophila wadsworthia (B. wadsworthia), Salmonella choleraesuis (S. Choleraesuis), Salmonella Typhimurium (S. typhimurium), Escherichia coli (E. coli) and Brachyspira Hyodysenteriae (B. hyodysenteriae). IFA and IHC results indicated that the monoclonal antibodies can be successfully used as primary antibodies to detect L. intracellularis in infected cells and in crypt of the ileum from infected tissues of PE. Our findings suggested the new monoclonal antibody specific against L. intracellularis will be useful for the evaluation of L. intracellularis infection in vivo and in vitro.